The Calorie Burning Calculation System in Jogging Using a Thresholding-Based Accelerometer Sensor - Okmayura, Finanta; Jefiza, Adlian; Ramadhani, Witri (Universitas Muhammadiyah Malang, 2020)
Jogging has benefits for burning calories as well as for losing the weight of the body. However, the reality that often happens is that sportsmen overwork their body in exercising so that it has passed its normal threshold. This causes over or lower calorie burning in these athletes. To overcome these problems, we need a device that can later monitor calorie burning. This device is created on an Android-based platform using an accelerometer sensor. Using this sensor, the system can count the number of a person’s steps previously obtained through the threshold value as the threshold value to determine the steps. Calculation of calorie burning uses a formula that involves the number of footsteps, time, and weight of the user. This application testing involved 15 participants by comparing the calorie burning results through the application and manual calculation, so that the overall error percentage of 0.60% was obtained, so it can be concluded that 99.40% of the calorie burning calculation system in jogging using a thresholding-based accelerometer sensor is appropriate for athletes to provide information of their calories burning in jogging.